Think fast! : accurate decision-making, problem-solving, and planning in minutes a day - Hale, Guy A. (Hoboken, NJ : Wiley, 2011)
Apply proven critical thinking processes and supercharge your business Alamo Learning Systems has been providing Critical Thinking Skills (CTS), problem solving, decision-making, preventive action, and innovation training solutions to the corporate world for more than 35 years
Includes index.
Keywords: Decision making; Problem solving; Critical thinking; Management